Six Sigma with C-K theory for innovations in operational excellence: a case study. Issue 7 (2nd September 2019) - Sony, Michael; Naik, Subhash
Abstract : Purpose: Six Sigma is a well-established powerful business strategy for achieving operational excellence (OPEX). However, previous studies have suggested that the Six Sigma may negatively impact organizational creativity and innovation. The C-K theory is one of the most widely used technique for design reasoning which promotes the creativity and innovation. The purpose of this paper is to integrate the Six Sigma methodology and C-K theory for enhancing innovative capacity of Six Sigma for achieving OPEX. Design/methodology/approach: The paper proposes an integration methodology of C-K theory and Six Sigma using the extant literature. Also, a case study is conducted based on the proposed integration model. Findings: The paper suggests a step-by-step integration methodology for integrating Six Sigma with C-K theory for both (DMAIC and DMADV). The methodology when applied to a live case in mining logistics the results are very encouraging. The solution was cost effective and also technically superior compared to previous solutions. Practical implications: The paper proposes a step-by-step methodology for the integration of Six Sigma with C-K tools. The methodology is practically applied in a live case. Organizations can use findings from this paper to implement an integration model of Six Sigma with C-K theory. Originality/value: This is the first paper that proposes an integration methodology of Six Sigma with C-K theory to enhance the innovation capability to achieve the OPEX.